2020
DOI: 10.1111/jdi.13394
|View full text |Cite
|
Sign up to set email alerts
|

Association of time in range, as assessed by continuous glucose monitoring, with painful diabetic polyneuropathy

Abstract: Aims/Introduction: This study aimed to evaluate the association between time in range (TIR) obtained from continuous glucose monitoring and the prevalence and degree of painful diabetic neuropathy. Materials and Methods: A total of 364 individuals with diabetic peripheral neuropathy were enrolled in this study. Sensor-based flash glucose monitoring systems were used to monitor the participants' glucose levels, and the glycemic variability metrics were calculated, including the TIR, glucose coefficient of varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 30 publications
0
48
0
1
Order By: Relevance
“…HbA1c has been the only prospectively evaluated tool for assessing the risk for diabetes complications. However, as TIR emerges as a new metric for assessing glycemic control in addition to HbA1c, numerous studies have reported TIR as a metric for correlation with diabetes complications (Table 2) [28][29][30][31][32][33]. At first, a TIR of target glucose and TAR computed from 7-point SMBG but not CGM were retrospectively investigated for retinopathy and microalbuminuria outcomes using DCCT data and the associations have been reported [34].…”
Section: Association Between Tir and Diabetic Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…HbA1c has been the only prospectively evaluated tool for assessing the risk for diabetes complications. However, as TIR emerges as a new metric for assessing glycemic control in addition to HbA1c, numerous studies have reported TIR as a metric for correlation with diabetes complications (Table 2) [28][29][30][31][32][33]. At first, a TIR of target glucose and TAR computed from 7-point SMBG but not CGM were retrospectively investigated for retinopathy and microalbuminuria outcomes using DCCT data and the associations have been reported [34].…”
Section: Association Between Tir and Diabetic Complicationsmentioning
confidence: 99%
“…Ranjan et al [ 31 ] proved the relationship between the two in the longitudinal study in T1DM. Also, TIR was reported to be associated with painful diabetic polyneuropathy [ 32 ]. However, the TIR cuff-offs for reducing diabetes complications are lacking.…”
Section: Ten Core Cgm Metrics and Ambulatory Glucose Profilementioning
confidence: 99%
“…Short-term GV was estimated by MAGE in CGM and was found to be independently associated with a higher risk of DPN with type 1 or 2 diabetes [70], but the study had a small sample size, which might not be able to evaluate patients with severe diabetes complications. Yang et al found that a decreasing level of TIR was significantly associated with an increasing risk of painful diabetic neuropathy, which might be underscored as a valuable clinical evaluation measure [71]. Investigators of a retrospective study reported that long-term variability as evaluated by FPG-CV was associated to the risk of painful DPN in patients with T2DM [72].…”
Section: The Role Of Gv In Dpnmentioning
confidence: 99%
“…5 As such, there should be more awareness in the use of CGM to help identify patients whose HbA1c may be ideal but fall short in the TiR target. This might have a positive impact on our diabetic care management because there are an increasing number of studies linking better TiR with lower rates of complications such as diabetic retinopathy 6,7 , peripheral neuropathy 8,9 and carotid intima thickness. 10 Technological advances in CGM opened up more windows of opportunity for coordination of care between physicians and patients in the primary care setting.…”
Section: Discussionmentioning
confidence: 99%